Biologic scaffold for CNS repair. (May 2014) - Meng, Fanwei; Modo, Michel; Badylak, Stephen F
Injury to the CNS typically results in significant morbidity and endogenous repair mechanisms are limited in their ability to restore fully functional CNS tissue. Biologic scaffolds composed of individual purified components have been shown to facilitate functional tissue reconstruction following CNS injury. Extracellular matrix scaffolds derived from mammalian tissues retain a number of bioactive molecules and their ability for CNS repair has recently been recognized. In addition, novel biomaterials for dural mater repairs are of clinical interest as the dura provides barrier function and maintains homeostasis to CNS. The present article describes the application of regenerative medicine principles to the CNS tissues and dural mater repair. While many approaches have been exploring the use of cells and/or therapeutic molecules, the strategies described herein focus upon the use of extracellular matrix scaffolds derived from mammalian tissues that are free of cells and exogenous factors.